1989
DOI: 10.1159/000234827
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Heterogeneity in the Small Intestine of Normal, Gnotobiotic and Parasitized Pigs

Abstract: A formalin fixative and a formalin-free fixative were used to study mast cells in the small intestine of conventional, gnotobiotic and parasitized pigs. Many more mast cells were identified after basic lead acetate fixation (‘mucosal mast cells’, MMC) than after routine formalin fixation (‘connective tissue mast cells’). The MMC were preferentially localized in the lamina propria. There were no differences between conventional and gnotobiotic pigs. However, in parasitized animals, the number of mast cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Information concerning pig mast cells is sparse *To whom correspondence should be addressed at: PHLS Centre for Applied Microbiology and Research, Division of Pathology, Porton Down, Salisbury, Wiltshire SP4 0JG, UK. 0018-2214 9 1993 Chapman & Hall (Ashraf et al, 1988;Pabst & Bell, 1989) and the aim of this study was to characterize porcine mast cells histochemically and morphologically before investigating their role in immune responses in infectious enteropathies of pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Information concerning pig mast cells is sparse *To whom correspondence should be addressed at: PHLS Centre for Applied Microbiology and Research, Division of Pathology, Porton Down, Salisbury, Wiltshire SP4 0JG, UK. 0018-2214 9 1993 Chapman & Hall (Ashraf et al, 1988;Pabst & Bell, 1989) and the aim of this study was to characterize porcine mast cells histochemically and morphologically before investigating their role in immune responses in infectious enteropathies of pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Three Göttingen minipigs were orally infected with larvae of A. suum (the porcine equivalent to human ascariasis) shortly after birth [32]. After 18 weeks, when mature nematodes were present in the intestine, the animals were killed together with 3 control minipigs to be used for a different study, which was conducted at the Medizinische Hochschule Hannover and corresponded to the ethical guidelines of that institution.…”
Section: Experimental Ascariasismentioning
confidence: 99%
“…Intestinal ascariasis was studied in 2 human cases and a porcine Ascaris suum infection model. Porcine and human intestines have been shown to bear a close resemblance to each other [32], to the extent that porcine grafts have proved suitable for use in transplantation surgery [see, for example, ref . 33].…”
Section: Introductionmentioning
confidence: 99%
“…in the skin 7-10 . In pigs, mucosal-type MCs and connective tissue-type MCs have likewise been described due to histochemical properties 11 . However, it is postulated that heterogeneity of MCs in tissues is much more diverse than merely two polarized phenotypes and is probably dynamically changing in accordance with micro-environmental conditions 3 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that staining patterns of MCs, including the porcine ones, are critically dependent on the respective fixation technique employed. 11,15-17 Apparently, the detection of MCs in formalin fixed specimens is dependent on the species and the localization. 16,18-21 In the pig, mucosal and submucosal MCs did not stain or stained only faintly after formalin fixation 11,17 and a similar phenomenon of loss of metachromatic staining of mucosal MCs is seen in rats and humans.…”
Section: Introductionmentioning
confidence: 99%